Kuat Tekan Dan Sorptivity Beton Dengan Serbuk Kulit Kerang (Anadara Granosa) - Reny Akmalia; Monita Olivia; Alfian Kamaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
This study examines the compressive strength and sorptivity of the concrete using powdered shells as a partial replacement of cement. Powder derived from the shells of shell types Anadara granosa who experience burning in the furnace brick and filtered using a sieve # 200. Variations shells used is 4% due to a variation of the optimum. After the trial manufacture of test specimens was performed to compare the nature of the powder concrete with normal concrete shells, then soaking for 7, 28 and 91 days. The results showed the strength of concrete shells powder is lower than normal concrete, concrete Sorptivity powdered seashells higher than normal concrete. From the results show the physical properties of concrete dust shells higher than normal concrete. This happens because the powder concrete shells have more pores and has a lower workability.Keywords: powder shells, Anadara granosa, compressive strength, sorptivity